Intelligent Production Machines and Systems : 2nd I*PROMS Virtual International Conference 3-14 July 2006. - Pham, Duc T. (Elsevier, 2007)
100 peer-reviewed articles from this key web-based conference in manufacturing in a convenient printed format.